An elementary and unified approach to program correctness - Bohórquez, Jaime (Springer, 2009)
We present through the algorithmic language DHL (Dijkstra-Hehner language), a practical approach to a simple first order theory based on calculational logic, unifying Hoare and Dijkstra’s iterative style of programming with Hehner’s recursive predicative programming theory, getting the “best of the two worlds” and without having to recur in any way to higher-order approaches such as predicate transformers, Hoare logic, fixed-point or relational theory.

Presentamos a través del lenguaje algorítmico DHL (Dijkstra-Hehner language), una aproximación práctica a una teoría simple de primer orden basada en lógica de cálculo, unificando el estilo iterativo de programación de Hoare y Dijkstra con la teoría recursiva de programación predicativa de Hehner, obteniendo “lo mejor de los dos”. mundos” y sin tener que recurrir en modo alguno a enfoques de orden superior como los transformadores de predicados, la lógica de Hoare, el punto fijo o la teoría relacional.
Keywords: Teoría de la Programación; Metodología de programación; Algoritmos; Theory of Programming; Programming Methodology; DHL; Algorithms